A new species of Nymphon Fabricius, 1794 (Pycnogonida: Nymphonidae) from northern Spain - Anna, Soler-Membrives; Tomás, Munilla (Zootaxa, 2011)
A new species of pycnogonid, Nymphon tricuspidatum, is described from a slope (574–610 m depth) on the NE Atlantic coast. Four males, two females, five juveniles and nine post-larvae were collected with suprabenthic and epibenthic sledges from Le Danois Bank (Bay of Biscay) and the Galician waters. This uniunguiculate and brevitarsal species is defined by the following exclusive features: a tricuspidated ocular tubercle, T-shaped frontal part of the cephalon, lateral implantation of the cheliphores, particular denticulation of the chela fingers, the 4 th palp article smaller than the 5 th , and the presence of 2 or 3 cement gland tubes. These characters distinguish the species from its most similar species Nymphon tubiferum, and the new species is compared to other similar species within the same genus, namely N. caementarum, N. prolatum, N, puellula and N. caldarium.